(3GdEWGQ GdbGfhfj dGfOeGL GdTQcGJ GdJLGQjI (B: s (3OQGSI ebGQfI GdbGfhf GdadSWjfj GdCQOfj(B: (3GdeUQj (B/ s - (3CMeO YHOGdhgGH SYjO CHhRjfIs; (3eMehO eNJGQ CMeO HQjQj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3JfGhdJ gPg GdOQGSI HGdHMK ehVhY (B( (3GdEWGQ GdbGfhfj dGfOeGL GdTQcGJ GdJLGQjI (B- (3OQGSI ebGQfI GdbGfhf GdadSWjfj GdCQOfj(B: (3GdeUQj (B): (3HGYJHGQg CMO GdehVhYGJ GdegeI GdeJYdbI HGdTQcGJ GdJLGQjI h PGJ GdCKQ GdcHjQ YdjgG(B. (3h bO YGdLg GdHGMK ef NdGd KdGKI CHhGH SHbgG aUd JegjOj(B. (3MjK YQV aj GdaUd GdJegjOj dJYQja GdGfOeGL h CfhGYg(B. (3Ke JfGhd fWGb JWHjb GdGfOeGL ef MjK Tcd GdTQcGJ GdOGNdI ajg h ZGjGJgG h LfSjGJgG(B: (3h cPdc GdWHjYI GdbGfhfjI ddGfOeGL h GdJaQbI Hjfg h Hjf HYV GdfXe GdeTGHgI(B. (3Ke JfGhd GdMOjK Yf JMbjb h EfLGR YedjI GdGfOeGLs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi h GdHMQis
(3HHdjhLQGajG(B: (3UaMGJ (B345-360s
Keywords: (3GdJMhd aj Tcd GdTQcIs; (3Gdfbd GdLRFj ddCUhds; (3GdGfOeGL hGdJCejes; (3GdGfOeGL hGdGfbSGes; (3GdbGfhf GdadSWjfj, GdbGfhf GdCQOfjs; (3GKGQ GdGfOeGLs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs